Image Recovery Pariwisata-Bencana di Lereng Merapi Dengan Memanfaatkan Teknologi Informasi - Tunjung Sulaksono; Atik Septi Winarsih (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2017)
The image recovery on post-disaster tourism is an important activity to restore tourism business back to normal. Unfortunately tourism actors do not have appropriate capacity to deal with and strategy to implement to. Mount Merapi eruption in 2010 resulting lodging business-owners in its slope areas hit by the drastic decline of tourist arrivals rate. Despite the recovery image activities are still conducted by the local government but those have not penetrated all the affected areas. Lodging owners have created their own efforts by creating web blog and producing related printing materials, yet those have not resulted in satisfying results since the involved information technology was still modest and has not been designed in interactive format yet. Moreover, the design of printed materials was too common. Based on these issues it is necessary to conduct community service activities to accelerate the image recovery efforts based on information technology. Those activities succeeded in enabling the business owners to create more interactive internet domain and eye-catching sign boards. To improve the competence of the manager or owner of lodge business, training has also been carried out in order to take into account the tourism risk and hospitality issues. Keyword: disaster-tourism, recovery image, information technology